Factors associated with low birth weight infants of teenage pregnancy in Terengganu, 2018 - Samsury, Siti Fatimah (2020)
Background: Teenage pregnancy is known to be associated with negative outcomes including low birth weight infant, preterm birth and anaemia. Identifying these outcomes and factors associated with low birth weight infants of teenage pregnancy may help to improve the prevention and management of these factors, and subsequently improve the pregnancy outcomes. Objective: This study aims to determine the obstetrics and perinatal outcomes of teenage pregnancy, and factors associated with low birth weight infants of teenage pregnancy in Terengganu in 2018. Methodology: A cross-sectional study was done from 1st January 2020 until 31st May 2020 using data from the Maternal Health Record Book and Pregnant Woman and Postnatal Book Registry. The source population were all teenage pregnancies attending government health clinics in Terengganu in 2018. Simple logistic and multiple logistic regression analysis was used to analyse the factors associated with low birth weight infants of teenage pregnancy. Result: All 357 cases that fulfilled the study criteria were included. The most common obstetric outcomes among teenage pregnancy was anaemia (41.5%), subsequently followed by caesarean section (10.9%), gestational diabetes mellitus (2.8%) and pregnancy-induced hypertension (1.4%). Low birth weight infants were the most common perinatal outcomes among teenage pregnancy (19.3%). It was followed by preterm birth (9.0 %) and both low Apgar score and stillbirth, 1.4% respectively. Factors associated with low birth weight infants of teenage pregnancy in Terengganu were teenage husband (AOR 2.0; 95% CI: 1.01, 3.96; p =0.047) and mothers with low education level (AOR 3.07; 95% CI: 1.20, 7.85; p =0.019). Conclusion: Teenage husband and low levels of mothers’ education were the significant associated factors that need to be addressed to improve teenage pregnancy outcomes. Interventions to improve these factors should continue to be encouraged.